O ensino de geometria plana pela resolução de problemas do tipo quebra-cabeças com palitos de fósforo - Lacerda, Geraldo Herbetet de (2011)
This research comprises the result of a process that had beginning as a personal reflection about a specific type of teaching activity that we had developed in the classroom, allowing us to expand our understanding of this topic and work with elements that can be explored in the process of initial and continuing training of teachers of Mathematics. Focusing on the teaching of plane geometry and more specifically exploring relative contents to the study of polygons such as classification, relation between properties, determination of perimeter and area, we take the van Hiele model as the main theoretical reference, which includes establishing different levels of development in student`s geometric thoughts, focusing on the first three (Levels 0, 1 and 2), connecting the action with manipulative materials for teaching geometry and solve problems. As a source of reflection for analysis, we take as the basic proposition a particular type of puzzles with matchsticks in Mathematics textbooks aimed at students from 6 to 9 Years of Elementary Education. We understand that the field of theoretical proposals as highlighted here for the teaching of geometry allows a teacher to do a better plan their actions to the classroom as well as more adequately explore the potential and limitations of various instruments, such textbooks, which are part of everyday school life. We concluded that even activities that may at first seem limited or traditional, can be improved considering references to research in a particular field of research, using them as a starting point for modifying the current reality of our formative student.